How much of Czestochowa is there in Częstochowa? The naming identity of the city - Jaros, Violetta (Papers in Linguistics, 2021)
The article reviews proper names functioning in the social space of Częstochowa, evoking associations with its history and topography. Its purpose is to provide a linguistic description of Częstochowa’s urbanonyms with their specific cultural references, which create local space, limiting the overwhelming influence of globalization. The characterized urbanonyms combine two contexts – physical and social space – and perform various functions: they serve as points of reference in the topography of the city and the region; they reflect the contemporary architectural structure and properties of the area and preserve the memory of the past ones; they commemorate distinguished residents of Częstochowa; and above all, they ensure identification with the city and strengthen distinctiveness of local space, shaping the collective identity of its inhabitants.